2012
DOI: 10.5194/acp-12-2631-2012
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in the fine-mode MODIS aerosol optical depth and its relationship to the changes in sulfur dioxide emissions in China between 2000 and 2010

Abstract: Abstract. Anthropogenic SO 2 emissions increased alongside economic development in China at a rate of 12.7 % yr −1 from 2000 to 2005. However, under new Chinese government policy, SO 2 emissions declined by 3.9 % yr −1 between 2005 and 2009. Between 2000 and 2010, we found that the variability in the fine-mode (submicron) aerosol optical depth (AOD) over the oceans adjacent to East Asia increased by 3-8 % yr −1 to a peak around [2005][2006] and subsequently decreased by 2-7 % yr −1 , based on observations by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 29 publications
(36 reference statements)
10
59
0
Order By: Relevance
“…In our previous studies (Itahashi et al, 2014a(Itahashi et al, , 2015, which considered data obtained in 2000-2011, emissions from China exhibited a transition from a continuously increasing trend. NO x emissions in China have been rising steadily (Kurokawa et al, 2013;Itahashi et al, 2014b), whereas SO 2 emissions in China peaked in [2005][2006] and subsequently declined due to the introduction of flue-gas desulfurization systems in China's 11th Five-Year Plan (2006 (Kurokawa et al, 2013;Itahashi et al, 2012). Recently, it has been reported that NO x emissions in China declined after 2011-2012 (Irie et al, 2016;Xia et al, 2016;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (Itahashi et al, 2014a(Itahashi et al, , 2015, which considered data obtained in 2000-2011, emissions from China exhibited a transition from a continuously increasing trend. NO x emissions in China have been rising steadily (Kurokawa et al, 2013;Itahashi et al, 2014b), whereas SO 2 emissions in China peaked in [2005][2006] and subsequently declined due to the introduction of flue-gas desulfurization systems in China's 11th Five-Year Plan (2006 (Kurokawa et al, 2013;Itahashi et al, 2012). Recently, it has been reported that NO x emissions in China declined after 2011-2012 (Irie et al, 2016;Xia et al, 2016;Krotkov et al, 2016;van der A et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CMAQ modeling systems have been used extensively for atmospheric environmental research over East Asia (e.g., He et al, 2007;Uno et al, 2007;Han et al, 2009;Itahashi et al, 2012aItahashi et al, , 2012bItahashi et al, , 2013. In this study, the meteorological fields were generated by the Weather Research and Forecasting (WRF) model version 3.3 with the National Centers for Environmental Prediction (NCEP)/National Center for Atmospheric Research (NCAR) reanalysis data (FNL; S. Itahashi et al: Regional modeling of tropospheric NO 2 vertical column density over East Asia 3625 http://rda.ucar.edu/datasets/ds083.2/).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The level over China was about tenfold that of Japan, and the level over Korea was almost twice that over Japan (Fig. 2 (e (Itahashi et al, 2012(Itahashi et al, , 2014a(Itahashi et al, , 2015. China, though these trends were not significant.…”
Section: Nss-somentioning
confidence: 91%